Endogenous t‐PA‐antigen is an independent predictor of adverse cardiovascular events and all‐cause death in patients with atrial fibrillation. Issue 6 (3rd July 2013) - Freynhofer, M. K.; Draxler, D. F.; Gruber, S. C.; Bruno, V.; Höchtl, T.; Fellner, B.; Jakl‐Kotauschek, G.; Wojta, J.; Pabinger‐Fasching, I.; Huber, K.; Ay, C.
Summary Background Atrial fibrillation (AF) is associated with raised levels of P‐selectin and an apparent prothrombotic state. However, levels of tissue plasminogen activator (t‐PA)‐antigen are increased also. We investigated whether high levels of endogenous t‐PA‐antigen or soluble P‐Selectin (sP‐Selectin), independently of CHADS2‐ or CHA2DS2VASc‐scores, predict major adverse cardiovascular events (MACE) in patients with AF when treated according to current guidelines. Methods This prospective, longitudinal single‐center study included 269 patients with AF. Blood samples were analyzed for sP‐Selectin and t‐PA‐antigen concentration by means of commercially available enzyme‐linked immunoassays. Results Patients were followed for a median duration of 1933 (1517–2277) days, during which 78 MACE and 82 deaths occurred. In multivariable analyses t‐PA‐antigen above the median of 4.22 ng mL−1 was associated with MACE and all‐cause death (HR 2.55 [1.43–4.57]; P = 0.002) and (HR 2.54 [1.38–4.68]; P = 0.003), respectively. There was no association of sP‐Selectin with MACE or all‐cause death. Furthermore, t‐PA‐antigen above the median independently of the CHADS2‐ or CHA2DS2VASc‐scores predicted MACE and all‐cause death. In patients with low and intermediate‐risk for cardiovascular events according to the CHADS2‐score the addition of high t‐PA‐antigen levels (> 4.22 ng mL−1) had a significant impact on the patients' outcome (low‐risk group, HR 3.25 [1.13–9.38]; P = 0.029 and intermediate‐risk group, HR 2.33 [1.27–4.26]; P = 0.006, respectively). Conclusion High endogenous t‐PA‐antigen independently predicts MACE and all‐cause death in patients with AF. Accordingly, t‐PA‐antigen as an indicator of a prothrombotic state represents a novel biomarker, which might add to risk stratification in patients with AF.